Food and Nutrition Justice: How to Make it More Newsworthy? - Thakurta, Paranjoy Guha; Chaturvedi, Subi (IDS bulletin (Brighton. 1984), 2012)
Growing corporatisation and commercialisation of the mass media in India and the world have resulted in facts and issues relating to food and nutrition justice being pushed to the fringes. In an environment where news‐gathering and gatekeeping processes result in a continuous tussle for prominence and stories have to be delivered under short deadlines, articles are measured against values such as currency, immediacy and impact on specific population segments. If complex and nuanced issues and facts on food and nutrition are to be highlighted, it would require consistent efforts on the part of advocacy groups to inform and sensitise media practitioners. This article explores how stories on food security and nutrition justice can be made more newsworthy and how opportunities can be optimised to bring greater prominence to reports and analytical articles on these subjects. It also elaborates on conflicts and discourses within the Indian media and civil society by critically examining reportage on these issues, and suggests ways in which to engage with the media.